2021
DOI: 10.1177/10986111211034777
|View full text |Cite
|
Sign up to set email alerts
|

Work–Family Conflicts, Stress, and Turnover Intention Among Hong Kong Police Officers Amid the COVID-19 Pandemic

Abstract: Although work stress, turnover intention, and work–family conflicts among police officers have been extensively investigated, no studies have explored these issues simultaneously under the context of the coronavirus pandemic. Clearly, both work and family domains have been drastically affected by this global health crisis, and it is likely that each domain has a distinctive impact on work outcomes. Using survey data based on a representative random sample of 335 police officers in Hong Kong, this study examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…Furthermore, WFC is perceived by resorts’ employees significantly and positively affects their turnover intentions, which is coincided with previous studies (i.e., Chen et al, 2018 ; Mansour and Tremblay, 2018 ; Park and Min, 2020 ) confirming that WFC is positively associated with turnover intentions. Moreover, this finding also supports the findings of Li et al (2021) who examined the impact of WFC on Hong Kong police officers’ turnover intentions during COVID-19 and concluded that WFC had significant and positive effects on turnover intentions (B = 0.143, p < 0.05). This finding is also relevant to Yucel et al (2021) , who found a significant and positive relationship between WFC and turnover intentions during the COVID-19 outbreak among public hospital employees in Erzincan province.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, WFC is perceived by resorts’ employees significantly and positively affects their turnover intentions, which is coincided with previous studies (i.e., Chen et al, 2018 ; Mansour and Tremblay, 2018 ; Park and Min, 2020 ) confirming that WFC is positively associated with turnover intentions. Moreover, this finding also supports the findings of Li et al (2021) who examined the impact of WFC on Hong Kong police officers’ turnover intentions during COVID-19 and concluded that WFC had significant and positive effects on turnover intentions (B = 0.143, p < 0.05). This finding is also relevant to Yucel et al (2021) , who found a significant and positive relationship between WFC and turnover intentions during the COVID-19 outbreak among public hospital employees in Erzincan province.…”
Section: Discussionsupporting
confidence: 86%
“…As a final point, strain-based conflict ensues once an individual feels anxiety due to one role which consequently leads to unsuccessful participation in another role. Work overload, exhaustion, and tensions from work conditions negatively affect the quality of employees’ home life stability ( Li et al, 2021 ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Organizational politics is both functional and dysfunctional in nature. This resemblance between two constructs demonstrates their close relationship (Li et al, 2021). The primary goal of my research thesis is to identify any potential relationships between these two important variables, as well as to investigate the conflict-politics outcome, to see how the two constructs influence attitudes and behaviors such as job stress, intention to quit, interpersonal and organizational workplace deviance (Gragnano et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research from (Y. on hospital nurses in China shows that work-family conflict will affect the turnover intention of nurses. In addition, (Li et al, 2022) conducted a study on 335 police officers in Hong Kong and found that the work-family conflict experienced by police officers would lead to their desire to leave the job. The same finding was also confirmed by several other studies ( (Zhou et al, 2020); (Aboobaker & Edward, 2020); (Chen et al, 2018)).…”
Section: Introdunctionmentioning
confidence: 99%